Diszkrimináció a munkaerőpiacon - Dajnoki, Krisztina; Balázs-Földi, Emese (Közép-Európai Közlemények, 2016)
In general, we speak about discrimination when a group is differentiated from the rest of the society either in negative or positive way. In the everyday life usually we consider negative differentiation under discrimination, which is frequently the consequence of prejudices. The requirements of equal treatment mean that it is forbidden to judge anybody adversely based on any of his/her characteristic or affiliation to a group, namely discriminate. In the Hungarian law the discrimination is already forbidden by the Constitution, however the general declaration become concrete through the act of Equal treatment which accurately defines the behaviours considered as negative discrimination, and if the differentiation described in the law occurred what kind of right enforcement has the discriminated victim. The article beside the definition of discrimination also clarifies its types and presents concrete employment-related discriminative legal cases. Our objective is to reveal the realization of discrimination through legal cases and protected attributes (sex, origin, age and disability), and to make suggestions so as to avoid illegal behaviour.